Anaplastic large cell lymphoma as a posttransplant lymphoproliferative disorder in a renal transplant patient: A case report - Manar Alabdulbaqi; Melissa Toupin; Philip Berardi; Arleigh McCurdy (eJHaem, 2020)
Abstract We report a case of a 45‐year‐old female who developed an ALK‐positive anaplastic large cell lymphoma (ALCL) 9 years after renal transplant. The patient underwent a cadaveric renal transplant for diabetic nephropathy, and presented 9 years later with fever and multiorgan dysfunction. The initial CT scans showed multiple enlarged supra‐ and infradiaphrgamatic lymph nodes. A CT‐guided core needle biopsy of a retroperitoneal lymph node revealed ALK positive ALCL. She received six cycles of cyclophosphamide, adriamycin, vincristine, etoposide, and prednisone, and has been in remission for over 3 years. Monomorphic T‐cell posttransplant lymphoproliferative disorder (PTLD) is an established but rare entity of PTLD and generally carries poor prognosis. This is a case report of a late PTLD with pathology reporting an aggressive T‐cell lymphoma that has been successfully treated with multiagent chemotherapy.